Characterisation and identification of phenolic compounds from Asparagus laricinus and Senecio asperulus (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2023)
Nature has been a good supply of medicinal agents for thousands of years, and more than 50% of modern drugs are derived from natural sources such as plants. Asparagus laricinus and Senecio asperulus have been used in traditional remedies to treat inflammation-related disorders and cancer. This study aimed to determine the chemical composition of A. laricinus and S. asperulus crude extracts using Liquid chromatography-mass spectrometry (LC-MS/MS) based untargeted analysis. The LC-MS-based untargeted analysis showed the phytochemical profile of A. laricinus cladodes and S. asperulus roots, of which twenty-nine phytochemicals from different chemical classes were annotated, including organic acids, phenolic acids, flavonoids, and other unknown compounds. Both these plants are used as traditional medicines, and their pharmacological benefits are due to their phytochemical profile and high phenolic content.